Correction: Atilan Fedai et al. Cardiac Clues in Major Depressive Disorder: Evaluating Electrical Risk Score as a Predictive Electrocardiography Biomarker. Medicina 2025, 61, 1026 - Ulker Atilan Fedai; Halil Fedai; Zulkif Tanriverdi (Medicina)
Error in Figure/Table [...]